Multiferroic behavior of gd based manganite - Sagar, S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Ferroelectrics, 2009)
Here we report the multiferroic nature of charge ordered manganite Gd0.5Sr0.5MnO3 for the first time. The temperature variation of dielectric constant shows broad relaxor type ferroelectric transition at around 210K and magnetization measurements shows weak ferromagnetism at 50K. The dielectric peak is very close to charge ordering temperature which is an evidence of the link between electronic state and increase of dielectric response. Butterfly variation of capacitance with voltage confirms ferroelectric nature of the sample at room temperature.
Keywords: dielectric constant; manganite; Multiferroic